Lamin B1 controls oxidative stress responses via Oct-1 - Malhas, A; Lee, C; Vaux, D (Rockefeller University Press, 2009)
Interactions of lamins with chromatin and transcription factors regulate transcription. Oct-1 has previously been shown to colocalize partly with B-type lamins and is essential for transcriptional regulation of oxidative stress response genes. Using sequential extraction, co-immunoprecipitation (IP), fluorescence loss in photobleaching, and fluorescence resonance energy transfer, we confirm Oct-1-lamin B1 association at the nuclear periphery and show that this association is lost in Lmnb1Δ/Δ cells. We show that several Oct-1-dependent genes, including a subset involved in oxidative stress response, are dysregulated in mnb1Δ/Δ cells. Electrophoretic mobility shift assay and chromatin IP reveal that Oct-1 binds to the putative octamer-binding sequences of the dysregulated genes and that this activity is increased in cells lacking functional lamin B1. Like Oct1 -/- cells, Lmnb1Δ/Δ cells have elevated levels of reactive oxygen species and are more susceptible to oxidative stress. Sequestration of Oct-1 at the nuclear periphery by lamin B1 may be a mechanism by which the nuclear envelope can regulate gene expression and contribute to the cellular response to stress, development, and aging.